2016
DOI: 10.3732/ajb.1600062
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salinity and flooding on post‐hurricane regeneration potential in coastal wetland vegetation

Abstract: Seed germination and subsequent seedling growth in coastal wetlands may in some cases be affected by salinity intrusion events even at low salinity levels (1 and 5 ppt). These results indicate that the potential is great for hurricanes to shift vegetation type in sensitive wetland types (e.g., maritime forest) if post-hurricane environments do not support the regeneration of extent vegetation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…For germination studies that tested flooding separately from salinity, however, flooding was also shown to decrease seedling emergence (Peterson and Baldwin 2004, Delgado et al 2018, Sloey and Hester 2019). Indeed, our measured coefficient of community was lowest between the SNF and SF treatments (0.32; Table 4), so both flooding and salinity are physical factors affecting seed germination and plant success (Middleton 2016).…”
Section: Discussionmentioning
confidence: 95%
“…For germination studies that tested flooding separately from salinity, however, flooding was also shown to decrease seedling emergence (Peterson and Baldwin 2004, Delgado et al 2018, Sloey and Hester 2019). Indeed, our measured coefficient of community was lowest between the SNF and SF treatments (0.32; Table 4), so both flooding and salinity are physical factors affecting seed germination and plant success (Middleton 2016).…”
Section: Discussionmentioning
confidence: 95%
“…Overwash occurs when foredunes are destroyed resulting in salt intrusion to inland communities, which reduces germination of salt intolerant species (Middleton 2016). Foredunes may offer protection to interior communities, depending on variations in elevation and length (Zarnetske et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the existence of a ridge on the eastern fringe of the Guiuan site provides partial protection for the inland area not only from the destructive power of the coastal flooding but also from the intense salinity induced by the coastal flooding. Middleton (2016) indicated that even a very low level of typhoon-induced salinity reduces the regeneration potential of the coastal vegetation [62]. However, the Guiuan site is expected to be exposed to higher salinity contamination and storm surge-related damages than the Tacloban site.…”
Section: Discussionmentioning
confidence: 99%